Spectral properties of novel transparent glass-ceramics based on Fe2+:ZnAl2O4 nanocrystals. (December 2020) - Eremeev, K; Dymshits, O; Alekseeva, I; Khubetsov, A; Zapalova, S; Tsenter, M; Basyrova, L; Loiko, P; Zhilin, A; Popkov, V
Abstract: Transparent glass-ceramics of the zinc aluminum silicate system nucleated by TiO2 and doped with FeO were developed by melt-quenching at 1580 °C with subsequent secondary heat-treatments at 720 – 1050 °C. The glass-ceramics based on nanosized gahnite crystals were characterized by X-ray diffraction, Raman and optical spectroscopy. The glass-ceramics exhibit a broad (1.5-2.5 μm) absorption due to the 5 E → 5 T2 ( 5 D) transition of Fe 2+ ions in Td sites in gahnite crystals. They are promising as saturable absorbers of the short-wave IR lasers.